IMAM AL-GHAZALI: PEMIKIRAN HUKUM EKONOMI ISLAM ABAD KE 5 H/ 11 M - Hamdan Firmansyah (TAHKIM, 2018)
In 1070 M Corpus Iuris Civilis, or "Book of Justinian", was rediscovered in northern Italy in the western region of Europe, most of the existing kingdom instituted a handful of remaining Roman institutions. The Crusade, which was first called for in 1095, is a military effort of Western European Christians to regain power over the Holy Land from Muslims. The development of Islam experienced a phase of progress in the year 650-1250 M which was marked by the very wide power of Islam, science and science experienced progress and unification between Islamic territories. In 1058, the great Islamic leader Imam al-Ghazali was born full name Abu Hamid Muhammad bin Muhammad al-Tusi al-Ghazali. He has contributed to the development of Islamic economic thought. Even his thoughts were utilized by thinkers afterwards in the world of Islam and non-Islam.